Measurement of Subpubic Angle in Radiograph - Kayastha, Prakash; Suwal, Sundar; Shrestha, leena; Paudel, Sharma; Shrestha, Shanta Lall; Joshi, Pramod (Nepalese Journal of Radiology, 2020)
Introduction: Subpubic angle, an important parameter used for sex determination in the pelvis, is the angle between two inferior pubic rami below the symphysis pubis. This study was carried out to determine the subpubic angle among the individuals referred for pelvic and KUB radiographs in the department of Radiology and Imaging, Tribhuvan University, Teaching Hospital. Methods: Prospective cross-sectional study was done on 120 individuals. The subpubic angle was measured by drawing two tangent lines on the inferior border of the pubic rami. The subpubic angle of both sexes was measured. An independent sample t-test for equality of means was used to determine the difference between the two sexes regarding the subpubic angle. The correlation between the subpubic angle and the age of subjects was obtained using Pearson Correlation Coefficients in males and females. Results: The range of the subpubic angle in male was 82o to 122° and the mean was 104.72°±10.47°. In females, the range was 96o to 159° and the mean was 137.15°±11.92° with a significant statistical difference from the angle in male (p<0.05). The subpubic angle was not significantly correlated with age in males (r=0.029, p=0.824) whereas, in females, the correlation of subpubic angle with age was significant (r=-0.303, p=0.019). Conclusion: The mean subpubic angle was significantly wider in females than in males in this study. We found a weak negative correlation between subpubic angle and age in females whereas in the male there was no correlation between age and subpubic angle.